Proliferative activity and apoptosis of Langerhans histiocytes in eosinophilic granulomas as evaluated by MIB-1 and TUNEL methods. Issue 5 (October 1995) - Hamada, Y; Iwaki, T; Fukui, M; Tateishi, J
Abstract : Aims —To identify the role played by apoptosis in tumour regression. Methods —The growth fraction and apoptotic cell loss of four cases of eosinophilic granuloma were investigated using monoclonal antibodies against Ki-67 proliferation marker (MIB-1) antigen and the TdT mediated dUTP-biotin 3′-OH nick end labelling (TUNEL) method. These data were then compared with the clinical growth rate. Results —Only the Langerhans histiocytic cells, which reacted positively with anti-S-100 protein antibody, were immunolabelled with antibodies to proliferating cell nuclear antigen and Ki-67 antigen (MIB-1). Many apoptotic figures of histiocytic cells were also detected in all cases by the TUNEL method. In a patient whose tumour clinically showed spontaneous regression, the TUNEL staining index gave a higher score than the MIB-1 staining index. Conclusions —The main cause of the spontaneous regression of the tumours was postulated to be programmed cell death (apoptosis).